EGFR Expression and its Association with Molecular Subtypes of Breast Carcinoma: A Cross-sectional Study - Anisa Barman; Suman Ghosh; Prasenjit Mukhopadhyay; Subhasish Bandyopadhyay; Anadi Roy Chowdhury (Journal of Clinical and Diagnostic Research)
Introduction: The incidence of breast carcinoma is rising worldwide. The Epidermal Growth Factor Receptor (EGFR) is a tyrosine kinase receptor that serves as an independent prognostic marker of poor clinical outcomes and aggressiveness in breast carcinoma. EGFR overexpression is specific to Triple-Negative Breast Cancer (TNBC). Therefore, the suppression of EGFR could potentially enhance the efficacy of TNBC treatment. Aim: To estimate the expression of EGFR in breast carcinoma and determine whether it is associated with aggressiveness (especially its correlation with tumour grade and proliferation index) and molecular subtyping based on Immunohistochemistry (IHC). Materials and Methods: This was a cross-sectional observational study conducted at Murshidabad Medical College and Hospital, Berhampore, West Bengal, India, from December 2022 to May 2024. A total of 31 confirmed breast carcinoma cases were studied. An IHC analysis was performed using biomarkers for Oestrogen Receptor (ER), Progesterone Receptor (PR), Human Epidermal growth factor Receptor 2 (HER2/neu), and Ki67 for molecular subtyping, along with EGFR to establish associations with subtypes. Results were analysed using the Chi-square test with Statistical Package for the Social Sciences (SPSS) version 20.0. Results: During the study period, 31 cases were examined, with a mean age of 54.91 years. Eleven cases (35.48%) showed EGFR overexpression. EGFR was significantly associated with grade 3 tumours (p-value=0.01) and a high Ki67 index (p-value=0.04). Conclusion: This study indicated that EGFR expression is an independent indicator of tumour aggressiveness. Its association with TNBC suggests that EGFR suppression therapy may be a preferred treatment option for TNBC.